2008
DOI: 10.1111/j.1567-1364.2008.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic evolution of a wine yeast during the first hours of fermentation

Abstract: The inoculation of active dry wine yeast (ADWY) is one of the most common practices in winemaking. This inoculation exposes the yeast cells to strong osmotic, acidic and thermal stresses, and adaptation to the new medium is crucial for successful fermentation. We have analysed the changes that occur in the ADWY protein profile in the first hours after inoculation under enological-like conditions at a low temperature. Protein changes mainly included enzymes of the nitrogen and carbon metabolism and proteins rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 34 publications
3
36
0
2
Order By: Relevance
“…While over 1,400 soluble proteins of yeast have been identified using 2-D analyses, this approach has not addressed the issue of quantification in a satisfactory manner and also suffers from the relatively low number of proteins which are identified in a single analysis, combined with an underrepresentation of low-abundance and hydrophobic proteins (17,35,36). In wine yeast, the 2-D gel approach coupled to mass spectrometry has been used to study postinoculation changes in protein levels (39) and the proteomic response of fermenting yeast to glucose exhaustion (45). Rossignol et al (36) used this approach to identify 59 proteins and compare the transcriptome and proteome of a single wine yeast strain during various stages of fermentation.…”
mentioning
confidence: 99%
“…While over 1,400 soluble proteins of yeast have been identified using 2-D analyses, this approach has not addressed the issue of quantification in a satisfactory manner and also suffers from the relatively low number of proteins which are identified in a single analysis, combined with an underrepresentation of low-abundance and hydrophobic proteins (17,35,36). In wine yeast, the 2-D gel approach coupled to mass spectrometry has been used to study postinoculation changes in protein levels (39) and the proteomic response of fermenting yeast to glucose exhaustion (45). Rossignol et al (36) used this approach to identify 59 proteins and compare the transcriptome and proteome of a single wine yeast strain during various stages of fermentation.…”
mentioning
confidence: 99%
“…In fermenting yeast, the first forays into proteomics have been reported, usually in conjunction with transcriptomic or metabolomic analysis (Brejning et al, 2005;Salvadó et al, 2008). Such studies have increased our knowledge regarding the growth phases of fermenting yeasts, and have suggested new methodologies for optimization and control of growth during fermentation-based industrial applications.…”
Section: -Proteomicsmentioning
confidence: 99%
“…Proteomic studies have also been carried out to gain a better understanding of the fluctuations in the stress-related gene mRNA levels during biomass propagation and to correlate glycolytic enzyme activities with their corresponding protein levels. However, the proteomic data available from industrial processes are very limited and usually centre on bioethanol production (Cot et al, 2007;Cheng et al, 2008) or wine and beer fermentations (Trabalzini et al, 2003;Zuzuarregui et al, 2006;Salvadó et al, 2008;Rossignol et al, 2009). Recent proteomic studies performed by 2D-gel electrophoresis during wine yeast biomass propagation have revealed that several glycolytic enzyme isoforms increase during biomass production.…”
Section: Yeast Stress Along Biomass Productionmentioning
confidence: 99%